Ethyl 1-(2-hydroxyethyl)-2-[2-(methylsulfanyl)ethyl]-1H-benzimidazole-5-carboxylate - Hamzah, Nurasyikin; Ngah, Nurziana; Abd Hamid, Shafida; Abdul Rahim, Aisyah Saad (International Union of Crystallography, 2012)
In the crystal structure of the title compound, C15H20N2O3S, the hydroxy group is involved in the formation of O-HN hydrogen bonds, which link two molecules into a centrosymmetric dimer. Weak C-HO hydrogen bonds further link these dimers into chains propagating along the a axis. The crystal packing exhibits - interactions between the five- and six-membered rings of neighbouring molecules [centroid-centroid distance = 3.819 (2) Å] and short intermolecular SS contacts of 3.495 (1) Å.